Cultivating Religious Moderation through Ḥadīth Content in Junior High School: A Psychological Perspective on State and Al-Azhar Teaching Materials - Rochmawati, Nikmah; Musyafiq, Ahmad; Rika Novalina; Mohamad Maulana Magiman (Department of Qur'an dan Hadith Faculty of Ushuluddin and Philosophy UIN Sunan Ampel Surabaya, 2025)
The spread of intolerance and radicalism among adolescents has made the internalization of religious moderation increasingly urgent for basic and secondary education. This study examines the ḥadīth content of the Islamic Religious Education (PAI) teaching materials used in parallel at SMP Islam Al-Azhar 29 Semarang and its implications for cultivating moderation, viewed through a psychological lens. Through a qualitative content analysis and comparative reading of the two sets of materials, those of the Ministry of Primary and Secondary Education and those of the Al-Azhar Islamic Education Foundation (YPI Al-Azhar), the study classifies ḥadīth content into four fields (creed, jurisprudence, Islamic history and culture, and ethics) and assesses the strength of its implications for moderation. Three findings emerge. First, both sets present ḥadīths in two modes, explicit (with Arabic text, translation, and source) and implicit (paraphrase or attribution without them). Second, the Ministry materials show greater moderation potential by number of chapters, the YPI Al-Azhar materials by number of ethics-related ḥadīths. Third, the Ministry materials emphasize the social dimension of moderation, while the YPI Al-Azhar materials emphasize its ritual dimension. The two sets are therefore complementary, and their use is best reinforced by a psychological-pedagogical approach: experiential learning, modeling and habituation, and emotion regulation.